Analisis Sistem Pengelolaan Limbah Berbahaya dan Beracun (B3) Pabrik Filter Rokok PT. XYZ Kabupaten Sidoarjo - Adibhaskara, Achmad Rheiza; Amalia, Aussie (Jurnal Serambi Engineering, 2025)
The tobacco industry is a strategic sector that significantly contributes to the national economy; however, its operations also generate hazardous and toxic waste (B3) that poses a risk to the environment. The objective of this study is to evaluate the B3 waste management system that has been implemented by PT. XYZ, with a particular emphasis on the reduction and management of waste, with a focus on storage practices. A descriptive methodology was employed, combining direct observation and document analysis of existing conditions, which were then compared against the provisions of the Minister of Environment and Forestry Regulation No. 6 of 2021. The evaluation employed a Likert scale to assess the level of compliance with the regulations. The findings indicated that PT. XYZ has been identified as a producer of nine distinct categories of B3 waste, with the primary sources of these materials being attributed to various production activities and maintenance procedures involving machinery. The waste reduction aspect achieved a compliance score of 62.5%, which is categorized as "Good," while the storage aspect reached 95.45%, which is categorized as "Very Good." The overall score was determined to be 78.97%. These results suggest that, despite the effective implementation of waste storage practices, enhancements are necessary in the domains of reporting and the utilization of waste reduction technologies, with the objective of aligning with the principles of sustainable development.